Scattering problems and boundary conditions for 2D electron gas and graphene - Kadigrobov, A.M. (Физика низких температур, 2018)
Structure and coordinate dependence of the reflected wave, as well as boundary conditions for quasi-particles
of graphene and the two dimensional electron gas in sheets with abrupt lattice edges are obtained and analyzed
by the Green's function technique. In particular, the reflection wave function contains terms inversely proportional to the distance to the graphene lattice edge. The Dirac equation and the momentum dependence of the
wave functions of the quasi-particles near the conical points are also found by the perturbation theory with degeneracy in terms of the Bloch functions taken at the degeneracy points. The developed approach allows to formulated the validity criteria for the Dirac equation in a rather simple way. Використано техніку функцій Гріна для отримання граничних умов та для аналізу координатної залежності хвильової функції відбитої квазічастинки у графені та двовимірному електронному газі у разі, коли кристалічна гратка має різку межу. Показано, що відбита хвильова функція містить доданки, величина яких оберненопропорційна відстані до межі гратки графена. На основі теорії збурень у виродженому випадку виведено рівняння Діраку та отримано імпульсну залежність хвильової функції квазічастинки поблизу кінцевої точки спектру в термінах незбурених функцій Блоха в точках виродження. Розвинене наближення дозволяє сформулювати критерій справедливості рівняння Діраку відносно простим способом. Использована техника функций Грина для получения
граничных условий и для анализа координатной зависимости
волновой функции отраженной квазичастицы в графене и
двумерном электронном газе в случае, когда кристаллическая решетка имеет резкую границу. Показано, что отраженная волновая функция содержит слагаемые, величина которых обратно пропорциональна расстоянию до границы
решетки графена. На основе теории возмущений в вырожденном случае выведено уравнение Дирака и получена импульсная зависимость волновой функции квазичастицы
вблизи конической точки спектра в терминах невозмущенных функций Блоха в точках вырождения. Развитое приближение позволяет сформулировать критерий справедливости
уравнения Дирака относительно простым способом.